2014
DOI: 10.1038/cdd.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

Nemo-like kinase is critical for p53 stabilization and function in response to DNA damage

Abstract: The DNA damage response (DDR) acts as a protective mechanism for maintaining cell homeostasis. Nemo-like kinase (NLK) is a serine/threonine-protein kinase that has an important role in many pathways; however, its function in the DDR has not yet been defined. In our study, NLK-deficient HCT116 cells were found to be resistant to etoposide-induced cell death. We demonstrated that NLK is required for p53 activation in response to DNA damage. Remarkably, mechanistic studies revealed that NLK interacts with p53 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…We propose that this integrin may be integrated in the growing list of molecular determinants of the p53 tumorsuppressor activity. [61][62][63] Response to chemotherapy may be hindered by p53-mediated cell cycle arrest or senescence. 64,65 As shown here, functional inhibition of the α5β1 integrin may represent a new way to sensitize glioma cells to the p53-dependent proapoptotic effect of Nutlin-3a.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that this integrin may be integrated in the growing list of molecular determinants of the p53 tumorsuppressor activity. [61][62][63] Response to chemotherapy may be hindered by p53-mediated cell cycle arrest or senescence. 64,65 As shown here, functional inhibition of the α5β1 integrin may represent a new way to sensitize glioma cells to the p53-dependent proapoptotic effect of Nutlin-3a.…”
Section: Discussionmentioning
confidence: 99%
“…In response to these cascades, NLK phosphorylates several transcription factors, including STAT3, Lef-1, and c-Myb. Previously, we have shown that NLK plays a role in the DDR via p53 regulation (7). We also found that NLK negatively regulates nuclear factor kappa B (NF-B) activity by disrupting the interaction between the TAK1 complex and IB kinase ␤ (IKK-␤) (8).…”
mentioning
confidence: 95%
“…Plasmids expressing NLK and its mutants with the indicated tags were previously described (7). Mammalian expression plasmids containing Flag-ATF5 and its mutants were generated by cloning into pCDNA5/FRT/TO-Flag; HA-ATF5 and HA-luciferase (HA-Luc) were generated by cloning into pCDNA5/FRT/TO-HA.…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite so many years, many questions remain still open in order to fully understand the biological role and function of this transcription factor. This complexity raise from different angles, including for example its stability and degradation [32,33], its connection to micro-RNA [34,35] or its splicing isoforms [36,37]. In keeping with the progress in understanding p53 biology, significant progress is also under way on its potential therapeutic application [38,39].…”
Section: Discussionmentioning
confidence: 97%